‘connEcted caesarean section’: creating a virtual link between MOthers and their infanTs to ImprOve maternal childbirth experieNce – study protocol for a PILOT trial (e-motion-pilot) - Antje Horsch; David Desseauve; Karine Lepigeon; Fiona Corbaz; Emilie Boussac; Diana Gomes Dias; Sandra Marcadent (BMJ Open, 2023)
Introduction One-third of mothers rate their childbirth as traumatic. The prevalence of childbirth-related post-traumatic stress disorder (CB-PTSD) is 4.7%. Skin-to-skin contact is a protective factor against CB-PTSD. However, during a caesarean section (CS), skin-to-skin contact is not always feasible and mothers and infants are often separated. In those cases, there is no validated and available solution to substitute this unique protective factor. Based on the results of studies using virtual reality and head-mounted displays (HMDs) and studies on childbirth experience, we hypothesise that enabling the mother to have a visual and auditory contact with her baby could improve her childbirth experience while she and her baby are separated. To facilitate this connection, we will use a two-dimensional 360° camera filming the baby linked securely to an HMD that the mother can wear during the end of the surgery.Methods and analysis This study protocol describes a monocentric open-label controlled pilot trial with minimal risk testing the effects of a visual and auditory contact via an HMD worn by the mother airing a live video of her newborn compared with treatment-as-usual in 70 women after CS. The first 35 consecutive participants will be the control group and will receive the standard care. The next 35 consecutive participants will have the intervention. The primary outcome will be differences in maternal childbirth experience (Childbirth Experience Questionnaire 2) at 1-week postpartum between the intervention and control groups. Secondary outcomes will be CB-PTSD symptoms, birth satisfaction, mother–infant bonding, perceived pain and stress during childbirth, maternal anxiety and depression symptoms, anaesthesiological data and acceptability of the procedure.Ethics and dissemination Ethics approval was granted by the Human Research Ethics Committee of the Canton de Vaud (study number 2022–00215). Dissemination of results will occur via national and international conferences, peer-reviewed journals, public conferences and social media.Trial registration number NCT05319665.